Technical systems and techno-fonctional variability of Early Stone Age assemblages in East Africa and Europe. - (:unkn) unknown (My University, 2016)
This work aims to reconsider the common models for the peopling of Europe during the Lower Pleistocene from a technological point of view. The study focuses on the technology and functional variability of Oldowan assemblages from Koobi Fora FxJj-10 (East Turkana, Kenya, Fejej FJ-1 (Lower Omo Valley, Ethiopia) and Olduvai DK (Tanzania). Then we compared the results with the first evidence of Human presence in Europe, mostly known because of lithic assemblages. In Europe , we studied the lithic assemblages from Barranco Leon and Fuente Nueva 3 (Spain), Pirro Nord and Monte Poggiolo (Italy). In each region, the same technological features appear, based on simple technical criteria applied cautiously on the cores to produce a variety of flakes. Differences are highlighted inside each area depending on the flaking modality : independant flake production (each flake is one operation, that can be repeated on the same core as long as acurate angles are available) or reccurent flake production (continuous series of recurrent flakes). The choice of one modality or the other is playing a very important role in raw material selection, that influences the type and shape of raw materials selected. The selection is made on purpose, and not as an adaptation of natural constraints, as shown in most sites environment where all materials were equally available, but clear choices were made.On the other hand, flaking modality does not change the objectives of production and the techno-functional groups are very similar in all sites.We propose that this choice is a cultural trait that changes a lot what was up to now considered as low evolved and simple technology.The European peopling cannot be related to technological features. According to the data studied, there is no argument that enhance the arrival of an African population, and more arguments that sustain the technical convergence and independant development of stone tool technology during the Lower Pleistocene.Key
Keywords: African Research